2022
DOI: 10.1177/17531934221111641
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in distal interphalangeal joint arthrodesis in the hand: a retrospective study of 173 cases

Abstract: In this retrospective study we aimed to analyse the risk factors for complications after different methods of distal interphalangeal arthrodesis in the hand. Forty-four per cent were treated with K-wire/cerclage fixation, 46% with X-fuse® implants (Stryker GmbH, Selzach, Switzerland) and 10% with headless compression screws (HBS®-screw, KLS Martin Group, Tuttlingen, Germany). The median follow-up was 16 weeks (range 6–224). The overall complication incidence was 44% (minor complications 29% and major 15%). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…In cases of joint deformity or pre-existing instability, joint surgery is often recommended to obtain optimal results. [5][6][7][8] On the other hand, posttraumatic degenerative arthritis, especially in the presence of instability, sometimes requires the use of a prosthesis. 9 DIP joint destruction is caused by inflammatory or degenerative processes, sometimes also by posttraumatic injury, and can be easily diagnosed through clinical examination and radiographic examination.…”
Section: Introductionmentioning
confidence: 99%
“…In cases of joint deformity or pre-existing instability, joint surgery is often recommended to obtain optimal results. [5][6][7][8] On the other hand, posttraumatic degenerative arthritis, especially in the presence of instability, sometimes requires the use of a prosthesis. 9 DIP joint destruction is caused by inflammatory or degenerative processes, sometimes also by posttraumatic injury, and can be easily diagnosed through clinical examination and radiographic examination.…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus on which method should be used [5][6][7][8]. Fixation with a headless compression screw has been associated with slightly higher bone union rates, but it increases the risk of certain minor complications that do not affect the outcome (e.g., wound healing problems, dysesthesia, and long-lasting postoperative pain) [9]. A systematic literature review of 32 studies covering 1125 cases of DIP joint arthrodeses reported overall complication frequencies of 19% for headless compression screws and 13% for K-wires, while the results on bone union frequency ranged from 91-96% for the different methods [5].…”
mentioning
confidence: 99%
“…A systematic literature review of 32 studies covering 1125 cases of DIP joint arthrodeses reported overall complication frequencies of 19% for headless compression screws and 13% for K-wires, while the results on bone union frequency ranged from 91-96% for the different methods [5]. Moreover, a recent retrospective study suggested that the choice of surgical technique will affect the outcome, as headless compressions screw arthrodesis was associated with a signi cantly lower rate of major complications when compared with K-wire/cerclage [9].…”
mentioning
confidence: 99%
See 2 more Smart Citations